A evolução do dogma trinitário na igreja antiga (sec. I a V) - Morais, Francisco Sales de (2011)
This present text aims to investigate the evolution of the Trinitarian tent in the early church:the understanding that the early Fathers of the Trinity had while attempting to provide answers the h resies that rose up from the event Jesus Christ, above all, especially as regards his divinity – as well as the divinity of the Holy Spirit. These are positions taken by the Church in two separate significant stages of cultural production of the meaning of the Trinity,but with the same purpose. It followed up after the Councils of Nicea and Constantinople the effort of some priests, especially of St. Augustine in the systematization of the Trinitarian tent. We assume that are the internal heresies in the Church who are provoking the deepening and systematization of Trinitarian tent. Thus this present work searches the unity from the Augustinian analysis of the Trinity and the support that this is the main "church fathers".